1989
DOI: 10.1021/j100362a009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of methylene blue by sulfide ion in the presence and absence of oxygen: simulation of the methylene blue-O2-HS- CSTR oscillations

Abstract: A mechanism is proposed that reproduces in simulations the oscillations seen during the methylene-blue-catalyzed reduction of 02 by HS" in a continuous-flow stirred tank reactor (CSTR). It contains 14 reactions and is based on experiments and simulations of simpler reactions, including the reduction of MB+ by HS" in the presence and absence of 02 and the reactions of H202 and 02 with HS". All experiments on component reactions as well as the CSTR oscillations can be simulated by the same set of reactions and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
4
21
0
Order By: Relevance
“…It has previously been reported in the literature that H2S reacts with H2O2 (reactions 3.2 and 3.3) as well as other radiolytic oxidants. As can be seen, H2O2 reacted rapidly with sulfide, which is in line with the reported rate constant 0.5 M -1 s -1 [94][95][96]. The stoichiometry for the reaction between H2O2 and sulfide was found to be 3:1, which is in agreement with the reported ratio [96].…”
Section: H 2 O 2 -Induced Dissolutionsupporting
confidence: 88%
“…It has previously been reported in the literature that H2S reacts with H2O2 (reactions 3.2 and 3.3) as well as other radiolytic oxidants. As can be seen, H2O2 reacted rapidly with sulfide, which is in line with the reported rate constant 0.5 M -1 s -1 [94][95][96]. The stoichiometry for the reaction between H2O2 and sulfide was found to be 3:1, which is in agreement with the reported ratio [96].…”
Section: H 2 O 2 -Induced Dissolutionsupporting
confidence: 88%
“…Although we were able to separate LMB from MB in an artificial test mixture we could not determine both analytes in a single run from urine samples probably due to the fast oxidation of LMB to MB [7][8][9] and lacking LMB standard substance. In this context, we observed that colourless acidic solutions of LMB turned blue upon the addition to surplus urine after a few minutes which is in agreement with earlier findings [8,9].…”
Section: Reduction Of Mb In Aqueous Ascorbic Acid Solutionsmentioning
confidence: 99%
“…LMB is not available as a standard substance and has only been obtained by diluting MB-solutions with reducing agents [4,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Present experimental results suggest that in the rate-limiting step, toluidine blue reac- tion with phenyl hydrazine involves a two-electron reduction step. A one-electron reduction of toluidine blue would have resulted in fractional-order with respect to [6,10,11]. Based on the kinetic results ϩ TB and the reaction products, the following mechanistic steps may be proposed for the reaction sequence.…”
Section: Mechanismmentioning
confidence: 99%